THE USE OF MUSIC AUDIO MEDIA (SONGS) IN LEARNING ARABIC AT SDS IT AL-AZHAR PLERED - Munir, Dede Rizal; maftuhah, maftuhah (STAI Bani Saleh, 2023)
This research is motivated by the large number of students who think that learning Arabic tends to be boring. Thus, the role of learning media is needed by educators and students so that a teaching and learning process can be carried out more easily to understand the material, and foster students' learning interest. The use of songs in simple language in learning Arabic will help students understand the material easily. This study aims to determine and identify the effect of using song media in learning Arabic at SDS IT Al-Azhar Plered. The method used in this research is qualitative by way of observation, interviews. Data was collected through observation techniques, interviews with Arabic subject teachers and also with students. The results showed that Arabic learning activities using songs in Arabic learning at SDS IT Al-Azhar Plered had a big impact on students, namely making it easier for students to understand by singing while learning